Effectiveness of social media and face-to-face family-based intervention in improving adiposity among Malay school children in Bangi, Selangor, Malaysia - Ahmad, Norliza (2017)
Background: Childhood obesity causes short- and long-term health problems and its increasing prevalence demands urgent public health action. Parents can play an important role in combating childhood obesity and social media may be an effective way of delivering family interventions. Objective: To develop, implement and evaluate the effectiveness of a family intervention based on REDUCE (REorganising Diet, Uncontrolled sCreen time and Exercise) delivered face- to-face and via social media, aimed at improving child adiposity that include BMI z-scores (primary outcome), waist circumference percentile (secondary outcome), and percentage body fat (secondary outcome) and intervening variables: i) parental factors (knowledge about nutrition, physical activity and obesity-related diseases; healthy lifestyle practices; authoritative feeding style; self-efficacy); ii) child factors (eating behaviour; consumption of sugar-sweetened beverages, fruit andvegetables, and unhealthy snacks; physical activity; screen time). Methodology: A two-arm, double-blind, randomised controlled field trial, involving parent-child dyads from five schools in Bangi, Selangor. Parents were eligible if (a) their children were aged between seven and ten years at recruitment, with BMI z-scores at least +1SD and (b) they were computer literate, had access to the Internet and were willing to use social media. Parents were excluded if their children had a chronic medical illness, physical or learning disabilities. All eligible parent-child dyads (134 parent-child dyads) were randomly allocated to intervention group (67 parent-child dyads) or the wait-list control group (67 parent-child dyads). The REDUCE intervention programme was based on social cognitive theory and was delivered in two phases. Phase one was a four-week training programme consisting of two face-to-face sessions and two Facebook contacts; phase two consisted of weekly boosters delivered via WhatsApp over a three-month period. Factor analysis and reliability of the questionnaire were conducted before collection of data. Data consisted of validated self-administered parental questionnaires, three-day food records and measurements of children’s height, weight and percentage body fat at baseline, immediately post-training, and at three- and six-months post-training. Data were analysed using generalised linear mixed models with covariates (child’s age, child’s gender, parents’ BMIs, parents’ education, family income, and baseline measurements), implemented in SPSS version 22. The level of significance was set at alpha = 0.05. Subgroup analyses were performed for overweight and obese children. Results are presented for the whole sample and for subgroups of overweight and obese children. Results: The response rate was 91%. At the six-month post-training, the intervention group had significantly reduced BMI z-scores compared to the wait-list group for the whole sample (F(6, 517) = 2.817, p = 0.008) and obese subgroup (F(6, 297) = 6.072, p <0.001). Waist circumference percentile was significantly reduced in the intervention group compared to the wait-list group for obese subgroup (F(6, 297) = 3.998, p = 0.001). The percentage of total body fat was significantly reduced compared to the wait-list group (F(6, 201) = 2.526, p = 0.022) for overweight subgroup. There were also significant differences between the intervention and control groups with respect to parental and child factors. The intervention group showed an increase in total parental knowledge score (whole sample; obese subgroup; overweight subgroup), improvements in dietary practice (whole sample; obese subgroup), improvements in physical activity practices (whole sample; obese subgroup), increased self-efficacy with respect to their child’s physical activity (whole sample; overweight subgroup) and a more authoritative parenting style (overweight subgroup). With respect to child factors the intervention group showed decreased enjoyment of food (whole sample; obese subgroup; overweight subgroup) and increased fruit and vegetable intake (whole sample; obese subgroup). Conclusion: The four-month REDUCE intervention programme, which was delivered face-to-face and via social media, was effective in reducing children’s adiposity for both overweight and obese subgroups and improving some of the parental factors and child factors associated with excess weight. These results suggest that the REDUCE intervention programme can be incorporated into child obesity prevention programmes delivered by primary health care centres.